Effect of low-dose dopamine on depression score in patients with heart failure - Kıvrak, Tarık (The European Research Journal, 2019)
Objective. This study aimed to assess the effects of low-dose dopamine on patients with depression in the intensive coronary unit. Methods: Relatives of 43 ICU patients enrolled in the study. Sociodemographic characteristics of patients and their families recorded. Patients evaluated basal echocardiographic and biochemical values measured in the patient group. The Beck Anxiety and Depression Scale was used to assess anxiety and depression. The assessment performed by Beck scale at the 1stand 24th hour. Results: The final study population consisted of 42 patients hospitalized with heart failure. Mean patient age was 67.5 ± 12.6 years. Average EF was 23.5% ± 8.7% and mean ProBNP was 6343.76 pg/mL in our study population. Changes of before and after dopamine treatment in depression score of heart failure patients was showed significantly (before value: 18.95 ± 9.89; after value: 17.29 ± 10.30, p < 0.001) however systolic and diastolic pressure difference was not significant. Conclusion: Depression increased mortality and hospitalization in patients with heart failure. Therefore, it is an essential trial because of low-dose dopamine improve depression score in intensive care patients. However, prospective studies were needed to assess the long-term efficacy of dopamine.